Nella terra dei melograni : Itinerari di turismo culturale nell'Albania del Nord - Monica Meini (Firenze University Press, 2006)
Northern Albania, the "land of the pomegranates", is a region where culture and nature are intimately bound up. This hypertext is proposed as an innovative tool of scientific divulgation for the valorisation of this precious and little-known territory, while also lending itself to various types of exploitation for tourist purposes. The itineraries, which radiate outwards from the city of Scutari, are presented through synthetic factsheets, composed using a simple and immediate language, and deriving from direct observation. Precisely because of its multiple functions, the hypertext has been organised at a number of levels: from simple description to historic and literary references or the reports of travellers, through to the detailing of the tourist resources available.
Keywords: Itinerari turistici; Geografia; Turismo; Albania